Qualidade tecnológica da farinha de trigo de grão inteiro parcialmente substituída por malte de trigo - Cauduro, Tatiana (2019)
Whole wheat flour (WWF) contains all components of intact grain and is recognized for its health benefits. These components are present in the grain external layers, in the fraction called bran. The bran promotes technological quality changes of wheat flour and the new technologies study for application in products are necessary in order to minimize the unwanted effects caused by the bran. The use of wheat malt flour may alter the whole wheat flour technological characteristics. The germination time and the proportion of wheat malt flour used may interfere with the technological characteristics of mass formation in bakery products, as well as to increase bioactive compounds. The aim of this study was to investigate the effect of the use of wheat malt flour on the technological and functional properties of pasta and pan bread made with whole wheat flour. The wheat of the cultivar Ametista, harvest 2016/2017, was dried up to 13% moisture. The germination was conducted at 20 ° C for 24, 48 and 72 h. The characterization of malt flour (MF) and whole wheat flour (WWF - control) was performed. After characterization, a completely randomized design in a 3 x 3 factorial arrangement was used. The malt flour germinated for 24, 48 and 72 hours were added in the proportions of 5, 15 and 25%, and wheat germ wheat flour not germinated as a control. The results were analyzed using the analysis of variance and the means compared by the Tukey test at 95% confidence interval. Total amylolytic activity, α-amylase and antioxidant activity increased in the malt flour as the germination time increased, in addition to a darker coloration in relation to the control sample. There was a decrease in the water absorption values, stability and time of mass development, as well as changes in the starch gelatinization profile in malt flour. When the factorial was applied, it was observed that, despite the increase in enzymatic activity, the number of fall values remained adequate for breads. A decrease in the viscosity of the gels when using flours from 48 h of germination together with a lower tendency to retrograde the same samples was observed. The stability of the masses decreased as the intensity of the substitution increased. The breads became softer with the use of MF 24 and MF 48 up to 15% replacement. Although it aided in increasing the volume of breads, the addition of MF 72 significantly increased the parameters of hardness and chewiness. There was a significant increase in the firmness of the loaves with increasing days of storage for all the experiments. The malting had a beneficial effect when flours were used with 48 h of germination in replacements of up to 15% and with 72 h until 5%, as they favored the increase of loaf volume and more homogeneous alveolar formation.